Does aging affect the formation of new topographical memories? Evidence from an extensive spatial training. Issue 1 (2nd January 2017) - Nemmi, Federico; Boccia, Maddalena; Guariglia, Cecilia
ABSTRACT: A decline in navigational abilities is a consistent feature of aging. Although many studies focused on recall of navigational information, the impact of time and type of learning on recall has received little attention. We submitted older adults and young participants to an extensive training of an ecological environment, from both route and survey perspectives. Then, we tested participants' learning using from both route and survey perspectives. Although older adults benefit from the extensive training, they did not reach the same performance of the young participants. Despite this main effect of age, the effect of the type of learning was the same in the two groups. Congruence between type of learning and recall led to better performance in both groups. We discuss these findings in the light of cognitive models of human navigation and aging. Useful suggestions about how these findings may inform a specific cognitive intervention in older adults are also provided.